2008
DOI: 10.1186/1744-8069-4-62
|View full text |Cite
|
Sign up to set email alerts
|

Origins, Actions and Dynamic Expression Patterns of the Neuropeptide VGF in Rat Peripheral and Central Sensory Neurones Following Peripheral Nerve Injury

Abstract: Background: The role of the neurotrophin regulated polypeptide, VGF, has been investigated in a rat spared injury model of neuropathic pain. This peptide has been shown to be associated with synaptic strengthening and learning in the hippocampus and while it is known that VGFmRNA is upregulated in dorsal root ganglia following peripheral nerve injury, the role of this VGF peptide in neuropathic pain has yet to be investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 25 publications
(35 reference statements)
2
46
1
Order By: Relevance
“…In SOD1 G93A transgenic mice, the VGF content in SMI-32 immunopositive spinal motor neurons was reduced in asymptomatic animals (approximately 75 days), and continued to decline as animals weakened (Zhao et al, 2008). A densely immunoreactive sensory projection reaches the superficial laminae of the dorsal horn (Ferri et al, 1992), in which VGF is co-localized with substance P and partly with CGRP, as shown in dorsal root ganglia or their cultures (Moss et al, 2008;Rizzi et al, 2008). However, things are probably more complex, since the expression of VGF mRNA in spinal ganglia is indeed intense in small diameter primary sensory neurons, but by no means absent in larger diameter, neurofilament protein expressing neurons (Ferri et al, 1997).…”
Section: Spinal Cord and Sensory Neurons Sympathetic Neuronsmentioning
confidence: 86%
See 1 more Smart Citation
“…In SOD1 G93A transgenic mice, the VGF content in SMI-32 immunopositive spinal motor neurons was reduced in asymptomatic animals (approximately 75 days), and continued to decline as animals weakened (Zhao et al, 2008). A densely immunoreactive sensory projection reaches the superficial laminae of the dorsal horn (Ferri et al, 1992), in which VGF is co-localized with substance P and partly with CGRP, as shown in dorsal root ganglia or their cultures (Moss et al, 2008;Rizzi et al, 2008). However, things are probably more complex, since the expression of VGF mRNA in spinal ganglia is indeed intense in small diameter primary sensory neurons, but by no means absent in larger diameter, neurofilament protein expressing neurons (Ferri et al, 1997).…”
Section: Spinal Cord and Sensory Neurons Sympathetic Neuronsmentioning
confidence: 86%
“…Conversely, intrathecal injection of the longer peptide TLQP-62 induced long lasting mechanical and cold allodynia (Moss et al, 2008). Upon axotomy, dorsal root ganglion neurons showed substantial accumulation of VGF peptides, both in culture (Ferri et al, 1997;Riedl et al, 2009), and in vivo (Riedl et al, 2009).…”
Section: Sensory Nerves and Painmentioning
confidence: 97%
“…A peripheral injection of TLQP-21 (residues 557 to 576 of VGF) was shown to increase the pain-related licking response in a mouse model (24). The intrathecal application of TLQP-62 (C-terminal 62 amino acids of VGF) to naive rats was found to cause long-lasting mechanical and cold behavioral allodynia (25). AQEE-30 and LQEQ-19, corresponding to the last 30 and 19 amino acids of VGF, respectively, were also shown to evoke thermal hyperalgesia in rats (26).…”
Section: Discussionmentioning
confidence: 99%
“…VGF and peptides derived from its proteolytic processing have been implicated in the control of energy balance and metabolism as well as in neuroplasticity associated with learning, memory, depression, and chronic pain [9,19,20,22,28,35,43]. …”
Section: Introductionmentioning
confidence: 99%
“…TLQP-62 [9]), and dorsal horn neurons (i.e. TLQP-62 [28]). Furthermore, intrathecal administration of C-terminal VGF peptides results in thermal hyperalgesia (i.e.…”
Section: Introductionmentioning
confidence: 99%